2021
DOI: 10.1016/j.stemcr.2021.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Patient-Matched PDOs Revealed a Reduction in OLFM4-Associated Clusters in Metastatic Lesions in Colorectal Cancer

Abstract: Metastasis is the major cause of cancer-related death, but whether metastatic lesions exhibit the same cellular composition as primary tumors has yet to be elucidated. To investigate the cellular heterogeneity of metastatic colorectal cancer (CRC), we established 72 patientderived organoids (PDOs) from 21 patients. Combined bulk transcriptomic and single-cell RNA-sequencing analysis revealed decreased gene expression of markers for differentiated cells in PDOs derived from metastatic lesions. Paradoxically, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Cellular heterogeneity of metastatic CRC has been recently studied by bulk transcriptomic and scRNA-seq analyses of primary and metastatic PDOs. The authors found that metastatic PDOs show decreased expression of differentiated markers and, curiously, also of intestinal stem cell markers, demonstrating that primary and metastatic lesions have distinct cellular composition [ 93 ].…”
Section: Organoids As a Model To Study Crcmentioning
confidence: 99%
“…Cellular heterogeneity of metastatic CRC has been recently studied by bulk transcriptomic and scRNA-seq analyses of primary and metastatic PDOs. The authors found that metastatic PDOs show decreased expression of differentiated markers and, curiously, also of intestinal stem cell markers, demonstrating that primary and metastatic lesions have distinct cellular composition [ 93 ].…”
Section: Organoids As a Model To Study Crcmentioning
confidence: 99%
“…This protocol describes the knock-in of the marker cassette into the OLFM4 locus, which we identified as stem cell markers of PDOs established from CRC ( Okamoto et al., 2021 ). However, we have also successfully used this protocol to visualize and evaluate their progeny.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…PDOs were embedded into Matrigel on glass-bottom plates and cultured for three days with (B) or without AP20147 (C). Note that EGFP expression of PDOs was decreased (B), because OLFM4-postive stem cells reduced their self-replication potential late after passage ( Okamoto et al., 2021 ). …”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations